Vesicle-Associated Membrane Protein-Associated Protein A Is Involved in Androgen Receptor Trafficking in Mouse Sertoli Cells - Qiong Deng; Jianwen Zhang; Zhu Wang; Shengping Zhang; Fan Zhi; Hui Liang (International Journal of Endocrinology)
Androgen and its receptor (AR) play an important role in maintaining spermatogenesis and male fertility. The nonclassical androgen signaling pathway is proposed to be mediated by an AR in plasma membrane in Sertoli cells. Our previous studies showed that testosterone induces cytoplasmic AR translocation to plasma membrane by binding with caveolin-1. This study was conducted to the underlying molecular mechanism mediating AR trafficking. Data from mass spectrometry using membrane coimmunoprecipitation sample by anti-AR antibody indicated VAPA is a candidate protein. Knockdown of VAPA by shRNA decreased the amount of AR localized to membrane and nuclear fraction and prevented AR trafficking after being exposed to testosterone. Further studies indicated AR trafficking in Sertoli cells might be mediated by VAPA via association with vesicle transport protein OSBP. This study can enrich the mechanism of the androgen actions and will be helpful for further clarifying the nonclassical signaling pathway of androgens in Sertoli cells.